Humans rather than climate the primary cause of Pleistocene megafaunal extinction in Australia - Sander van der Kaars (Nature Portfolio, 2017)
Megafaunal extinction in Australia has been attributed to both climate change and human causation. Here, van der Kaarset al. present a 150,000 year record offshore southwest Australia in which they refine the timing and nature of regional ecosystem changes and megafaunal population collapse.